Profil Hematologis Tikus Putih (Rattus novergicus sp.) Betina Setelah Pemberian Jamu Kesuburan - Rosdianto, Aziiz Mardanarian; Manalu, Wasmen; Maheshwari, Hera (Jurnal Farmasi Indonesia, 2016)
ABSTRACT: The use of herbal preparations to improve fertility were empirically beneficial for reproductive health, however its use needs to be supported by scientific evidence. In this study we observed the effects of herbal preparations on haematological parameters, liver function and kidney function of female rats. The estrus cycle of the experimental female rats were previously synchronized by injection with prostaglandin twice in two days interval. The rats were randomly assigned into eight groups i.e., two negative control groups, two positive control groups (injected with pregnant mare serum gonadotropin with effective and double of effective doses), two groups were given herbal preparation A (with effective and double of effective doses), and two groups were given herbal preparation B (with effective and double of effective doses). The treatments were given for 3 consecutive estrous cycles. Parameters measured were hematological parameters (erythrocyte, leukocyte, and hemoglobin), liver functions (SGOT and SGPT concentrations), and renal function (serum ureum concentration). The results showed that the administration of herbal preparation for fertility improved erythrocyte, leukocyte, and hemoglobin parameters, improved liver functions, and optimized renal functions. It was concluded that the administration of herbal preparation for fertility for 3 consecutive estrous cycles did not disturb physiological functions, instead its improved hematological parameters as well as liver and renal functions.Keywords: hematological, herbal, liver function, renal function, female rats Â ABSTRAK: Penggunaan jamu kesuburan secara empiris bermanfaat untuk kesehatan reproduksi, namun penggunaannya perlu didukung oleh data ilmiah. Dalam penelitian ini dilakukan pengamatan efek pemberian jamu kesuburan terhadap parameter hematologis, fungsi hati dan fungsi ginjal dari tikus betina. Penelitian ini diawali dengan sikronisasi siklus estrus tikus percobaan dengan penyuntikan prostaglandin dua kali dalam selang waktu dua hari. Tikus-tikus percobaan secara acak dibagi ke dalam delapan kelompok, yaitu dua kelompok kontrol negatif yang hanya diberi pelarut persiapan jamu kesuburan, dua kelompok kontrol positif yang disuntik pregnant mare serum gonadotropin untuk dosis efektif dan 2x dosis efektif, dua kelompok diberi jamu kesuburan A dengan dosis efektif dan 2x dosis efektif, dan dua kelompok yang diberi jamu kesuburan B untuk dosis efektif dan 2x dosis efektif. Perlakuan diberikan selama 3 siklus estrus berturut-turut. Parameter yang diukur adalah status hematologi (eritrosit, hemoglobin, dan leukosit), fungsi hati (kadar SGOT dan SGPT), dan fungsi ginjal (kadar ureum). Hasil penelitian menunjukkan bahwa pemberian jamu kesuburan memperbaiki parameter hematologis, memperbaiki fungsi hati, dan mengoptimalkan fungsi ginjal. Dari hasil penelitian disimpulkan bahwa pemberian jamu kesuburan selama tiga siklus estrus berturut-turut tidak mengganggu fungsi fisiologis tubuh bahkan terbukti memperbaiki parameter hematologis, fungsi hati, dan fungsi ginjal. Kata kunci: Jamu kesuburan, parameter hematologis, fungsi ginjal, fungsi hati, tikus betinaÂ